TERRAIN ESTIMATION PERFORMANCE OF ADVANCED SAR SATELLITES: COSMO-SKYMED AND TERRASAR-X - Sefercik, Umut Gunes; Yastikli, Naci; Atalay, Can (IEEE, 2017)
Presently, Cosmo-SkyMed (CSK) and TerraSAR-X (TSX) are the most advanced synthetic aperture radar (SAR) satellites which offer highest spatial resolution that could not be achieved from previous space-borne SAR missions. In addition to high spatial resolution both of them are capable of repeat-pass interferometry that makes possible three dimensional digital modelling of visible earth surface from space. In this study, digital earth modelling performance of CSK and TSX high resolution spotlight (HS) images is comprehensively analyzed regarding absolute and relative vertical accuracies of generated digital surface models (DSMs). Accuracies were calculated on different land classes in Istanbul using a reference DSM derived by airborne laser scanning (ALS). Compatible results were achieved for CSK and TSX in open, built-up, and forest land classes. The absolute vertical accuracies are between 8 m and 10 m considering standard deviation. The relative vertical accuracies are superior to absolute both for CSK and TSX as expected from active sensing.
Keywords: Cosmo-SkyMed; TerraSAR-X; High Resolution Spotlight; Interferometry; Airborne Laser Scanning; Engineering; Remote Sensing